Terminological Impoverishment: The Effects of Contemporary Scholarly Publishing Practices on Terminology and Knowledge Dissemination - Bowker, Lynne (TTR)

(untitled) (Association canadienne de traductologie, 2025)
Historically, translation played a key role in knowledge dissemination, but since the mid 20th century, scholarly publishing has moved steadily towards the use of a central language (English). Colonial practices, the incentivization of publishing in English, and the lag (or lack) of term development in other languages has led to the terminological impoverishment of many of these languages across multiple research domains. Consequences include the continued hegemony of English language and western culture and epistemologies, limited uptake of research findings in non-Anglophone communities, and a digital gap between English and other languages with regard to the development of linguistic resources and tools. Emerging approaches for addressing terminological impoverishment include terminology planning, retro-terminologization, broader consultation with communities (including Indigenous communities), and developing resources and tools for low-resource languages. In parallel, it is critical to recognize that reforms to research assessment are needed to value and encourage knowledge dissemination in languages beyond English, and that terminologists must raise the visibility of their profession and skills in order to be included in more efforts aimed at rectifying terminological impoverishment in scholarly research fields.